Reduced Expression of Galectin-8 May Contribute in Carcinogenic Pathway of Head and Neck Squamous Cell Carcinoma - Maryam Ghasemi; Laleh Vahedi Larijani; Jamshid azdani-Charati; Elham Kamali Hakim (Iranian Society of Pathology, 2021)
Background & Objectives: Galectin-8 has relationships with cell growth and metastasis of some cancers. Due to controversy in the clinical significance of this protein in the cancer process, we investigated its roles in the development of head and neck squamous cell carcinoma. Methods: This study was performed on 93 samples of patients with Squamous Cell Carcinoma or dysplasia of the head and neck, who underwent biopsy or surgery from 2015 till 2017 in Boo-Ali SINA hospital of Sari, Iran. The relevant paraffin embedded tissue blocks were obtained from archive of pathology and evaluated for galectin-8 by immunohistochemistry. The association between expression of galactin-8 and age, sex, location and stage of disease were assessed. To compare expression rate between the groups, Mc-Nemar, Chi-square and Fisher's exact tests were used. The P-value  Results: Strong cytoplasmic and nuclear galactin-8 staining was observed in 97.6% cases of normal tissues while 77% of dysplastic lesions and 69% of the cancers revealed negative immunoreactivity. The intensity of expression in dysplastic and malignant tissues was significantly reduced compared with normal tissues (p =0.0001). The expression of galectin-8 did not correlate with stage (p =0.303), lymph node involvement (p =0.326), tumor grade (p =0.769), distant metastasis (p =0.748), and age (p =0.574). Conclusion: We observed that the expression of galectin-8 in dysplastic and malignant squamous epithelium significantly reduced compared with the normal counterpart of them in the head and neck. It may contribute to malignant transformation of head and neck squamous cells.